RESPON TANAMAN SUKUN (Arthocarpus communiis Forst) TERHADAP PENGGUNAAN PELEPAH PISANG SEBAGAI MULSA ORGANIK PADA DTA DANAU TOBA, DESA PAROPO, KECAMATAN SILAHI SABUNGAN - Oscar Pardosi; Budi Utomo; Afifuddin Dalimunthe (Peronema Forestry Science Journal, 2016)
Lake Toba has indicated the existence of illegal logging in the area of Lake Toba and lowering the absorption capacity of rain forest. To support the growth of breadfruit, added water-retaining such as mulch. The mulch which use in this observation is Bananas frond mulch. This study aimed to look at the response of seedling growth breadfruit (Arthocarpus communiis Forst) on the provision of additional materials especially the bananas frond mulch to the growing media in the form of water-retaining materials. This study was conducted in November 2015-January 2016. The study was conducted at the watershed of Lake Toba,  the village Paropo, District Silahi Sabungan, Dairi. The result showed that there were interaction percentage of bananas mulching on the parameters observed. Percentage bananas mulch has significantly effect to the increase hight, number of leaves, and crown area. But did not has significantly effect to leaf area, and diameter. Keywords : Watershed of Lake Toba, Breadfruit (Arthocarpus communiis Forst), Bananas Frond Mulch, Retaining Water.